Cybercrimes And Social Media Addictions: The Role Of Perceived Use Of Conversational GPT-4 AI Model Among Residents In Nigeria - Onah, Caleb; Ogwuche, Chinelo Helen (Academic Journal of Psychology and Counseling, 2024)
The emergence of artificial intelligence (AI) affects several aspects of life. While AI has positive impacts, it also leads to adverse impacts such as the rise of gadget addiction and cybercrime. This study investigated the role of perceived usage of the conversational GPT-4 AI model in cybercrimes and social media addictions among residents in Makurdi Nigeria. The cross-sectional survey involved 200 participants who used the latest conversational GPT-4 AI model in their smartphones. Participants were selected using convenience sampling techniques. The results revealed a relationship between the usage of the conversational GPT-4 AI model and cybercrime incidence (R=0.255, R2=0.065, F(1, 189)=13.223, p< 0.01). The baseline usage of the conversational GPT-4 AI model was also found to significantly predict an increase in social media addictions (R=0.434, R2=0.188, F(5, 195)=24.147, p<0.01). The study also revealed that the usage of the conversational GPT-4 AI model was significantly associated with an increase in both cybercrime and social media addictions (R=0.474, R2=0.226, F(2, 185)=5.991; p<0.01). Based on the study’s findings, there is a need to develop and deliver educational programs to inform users about the responsible use of AI technologies, including the GPT-4 model.